161k views
5 votes
Desperate for help lol

Desperate for help lol-example-1
User Xenvi
by
5.5k points

1 Answer

5 votes

Hi there! See the Identity below in the box:


\large \boxed{(f - g)(x) = f(x) - g(x)}

We are also given that:

  • f(x) = 0
  • g(x) = 7x+9

Substitute both values in the equation.


\large{(f - g)(x) = 0 - (7x + 9)} \\ \large{(f - g)(x) = - (7x + 9)}

Recall the property:

  • (-)(-) = +
  • (+)(+) = +
  • (-)(+) = -
  • (+)(-) = -

Same sign multiplying the same sign = + while opposite = -

Using the distribution property, distribute the negative sign in 7x+9. Since 7x+9 are positive for both terms - distributing in would turn the expression in negative form.


\large{(f - g)(x) = - 7x - 9}

Hence, the answer is -7x-9.

Questions about the problem and my answer or explanation can be asked through comment.

Furthermore, (f-g)(x) is like a factored form of f(x)-g(x).

Hope this helps, and Happy Learning! :)

User RoboKozo
by
5.4k points